2004
DOI: 10.1021/jo035723q
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Microwave-Assisted Synthesis of Unsubstituted and Modified α-Quinque- and Sexithiophenes

Abstract: The facile synthesis of poorly soluble unsubstituted and modified alpha-quinque- and sexithiophenes under microwave irradiation in the liquid phase is described. The use of microwave irradiation allowed these compounds to be prepared in a few minutes and at high yields by means of the Suzuki cross-coupling reaction. Unsubstituted sexithiophene was obtained in 10 min via the one-pot borylation/Suzuki reaction, purified according to a very simple procedure, and isolated in 84% yield. The efficient synthesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…Several research groups have reported other high-speed microwave-assisted transition-metal-catalyzed transforma-tions, such as Suzuki, [279] Heck, [280] Sonogashira, [281] Negishi, [282] and Liebeskind-Srogl reactions, [283] BuchwaldHartwig aminations, [284] and related reactions. [285] Bahn and Adolfsson have demonstrated that functionalized 2,5-dihydropyrroles can be obtained by microwavemediated ruthenium-catalyzed ring-closing metathesis (RCM).…”
Section: Addendummentioning
confidence: 99%
“…Several research groups have reported other high-speed microwave-assisted transition-metal-catalyzed transforma-tions, such as Suzuki, [279] Heck, [280] Sonogashira, [281] Negishi, [282] and Liebeskind-Srogl reactions, [283] BuchwaldHartwig aminations, [284] and related reactions. [285] Bahn and Adolfsson have demonstrated that functionalized 2,5-dihydropyrroles can be obtained by microwavemediated ruthenium-catalyzed ring-closing metathesis (RCM).…”
Section: Addendummentioning
confidence: 99%
“…9 Palladium-catalyzed Suzuki coupling of iodide 8 with 2-thiopheneboronic acid (9) afforded the intermediate 10 in 58% yield. 10 And formylation at C-2 position of thiophene by n-BuLi and DMF (68%) 11 and condensation of the resulting aldehyde with cyanoacetic acid in the presence of piperidine (78%) provided the organic dye 1. 12 Synthesis of organic dye 2 was summarized in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…zeneboronic acid (11) and then 2-thiopheneboronic acid (9) in 52% and 71% yield provided the intermediate 12.…”
Section: Scheme 3 Preparation Of Dyementioning
confidence: 99%
See 2 more Smart Citations